HOW DOES JAKARTA’S MILLENNIALS PERCEIVE THE FEAR OF COVID-19 OUTBREAK’S BEGINNING? - Suhendra, Suhendra (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2021)
Abstract. This article discusses emotional expression and experience of Jakarta millennials in perceiving fear at the beginning of the Covid-19 outbreak in Indonesia. This research was conducted through a case study method which was narrated descriptively. The initial concept led this research in finding data was the Extended Parallel Process Model theory proposed by Kim Witte and several supporting concepts in emotional communication. The results show that Jakarta millennials perceive fear as internal anxiety created by threats as an external danger. They consider Covid-19 as a frightening threat with a high level of vulnerability and severity that has an impact on health, economic and social aspects. They also have a high level of efficacy by having the understanding of Covid-19 and health protocols and efforts to implement them. Individual differences through media literacy and direct experience of Covid-19 are important aspects that encourage efficacy to achieve danger control from fear that change beliefs, intentions, attitudes and behaviors of Jakarta millennials in fighting the transmission of Covid-19 through the application of health protocols.Keyword: Fear; Covid-19; Millennial; Media; ExperienceAbstrak. Artikel ini membahas mengenai ekspresi dan pengalaman emosi milenial Jakarta dalam mempersepsi rasa takut pada awal wabah Covid-19 di Indonesia. Penelitian ini dilakukan melalui metode studi kasus yang dinarasikan secara deskriptif. Konsep awal yang mengantarkan penelitian ini dalam menemukan data adalah teori Extended Parallel Process Model yang diajukan Kim Witte dan beberapa konsep pendukung dalam komunikasi emosional. Hasil penelitian menunjukan bahwa milenial Jakarta mempersepsi takut sebagai kekhawatiran yang bersifat internal yang diciptakan oleh ancaman sebagai bahaya yang bersifat eksternal. Mereka menganggap Covid-19 sebagai ancaman yang menakutkan dengan tingkat kerentanan dan keseriusan yang tinggi yang berdampak pada aspek kesehatan, ekonomi dan sosial. Mereka juga memiliki tingkat efikasi yang tinggi dengan adanya pemahaman tentang Covid-19 dan protokol kesehatan serta upaya penerapannya. Perbedaan individu melalui literasi media dan pengalaman langsung terhadap Covid-19 merupakan aspek penting yang mendorong efikasi untu mencapai pengendalian bahaya dari ketakutan yang mengubah kepercayaan, intensi, sikap dan perilaku milenial Jakarta dalam melawan penularan Covid-19 melalui penerapan protokol kesehatan.Kata Kunci: Rasa Takut; Covid-19; Milenial; Media; Pengalaman